Major city evacuation planning using simulation modeling. Issue 4 (9th November 2015) - Kirby, Adam M.; Dietz, J. Eric; Matson, Eric T.; Pekny, Joseph F.; Wojtalewicz, Cliff
Abstract : Purpose: – This study aims to provide data on the optimal staff, materials, space and time resources required to operate a regional hub reception center, a "short-term facility with the goal to process and transport displaced survivors (evacuees) to temporary or permanent shelters following a catastrophic incident" (Bonabeau, 2002). The facility will process approximately 20, 000 evacuees over its entire seven-day duration following a disaster to assist in community resilience. Design/methodology/approach: – The study was performed using a model created using the computer simulation software, AnyLogic. The software allowed for simulations to be performed on each of the three criteria: minimizing the space needed to run the hub, minimizing individual throughput time and minimizing total operation time. Findings: – The results of the study demonstrated that the goals set forth by the Illinois-Indiana-Wisconsin Regional Catastrophic Planning Team could be improved upon and that the largest contributing factor to optimizing the regional hub reception center (RHRC) is finding the optimal number of total staff members to operate the facility. Originality/value: – The value of the study lies in creating a life-saving environment for evacuees who could otherwise not evacuate themselves. The assistance provided by the RHRC gives displaced survivors a safe and organized method for evacuating a large city after a disaster. The study shows how computer models can help improve resilience in an urban area by planning the most efficient methods for evacuating it should it be necessary.